Membangun Generasi Wirausaha Muda: Analisis Empiris Pembelajaran, Dukungan Institusional, dan Self-Efficacy Mahasiswa - Pardede, Henry Dunan; Saragih, Doris Yolanda; Simarmata, Poltak Pardamean; Sipayung, Rosintan; Tampubolon, Jusra; Prabowo, Ari; Simarmata, Hengki Mangiring Parulian (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
The role of students is very important in developing entrepreneurship. The research aims to determine the effect of learning and institutional support on entrepreneurial behavior with self-efficacy as a moderating variable. This research is quantitative research and the sample is all 32 STIE Mars Pematangsiantar students who have participated in the entrepreneurship program. The analysis used is the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show a significant positive influence of institutional support on entrepreneurial behavior, a significant relationship between learning and entrepreneurial behavior, a significant relationship between learning and self-efficacy, and a significant relationship between self-efficacy and entrepreneurial behavior. There is an insignificant relationship between institutional support and self-efficacy. With these findings, it is hoped that entrepreneurial learning and institutional support can contribute to the development of entrepreneurial strategies at the University.